Climate change will increase the naturalization risk from garden plants in Europe - Iwona Dullinger; Johannes Wessely; Oliver Bossdorf; Wayne Dawson; Franz Essl; Andreas Gattringer; Günther Klonner; Holger Kreft; Michael Kuttner; Dietmar Moser; Jan Pergl; Petr Pyšek; et al. (Global Ecology and Biogeography, 2017)
Aim Plant invasions often follow initial introduction with a considerable delay. The current non‐native flora of a region may hence contain species that are not yet naturalized but may become so in the future, especially if climate change lifts limitations on species spread. In Europe, non‐native garden plants represent a huge pool of potential future invaders. Here, we evaluate the naturalization risk from this species pool and how it may change under a warmer climate. Location Europe. Methods We selected all species naturalized anywhere in the world but not yet in Europe from the set of non‐native European garden plants. For this subset of 783 species, we used species distribution models to assess their potential European ranges under different scenarios of climate change. Moreover, we defined geographical hotspots of naturalization risk from those species by combining projections of climatic suitability with maps of the area available for ornamental plant cultivation. Results Under current climate, 165 species would already find suitable conditions in > 5% of Europe. Although climate change substantially increases the potential range of many species, there are also some that are predicted to lose climatically suitable area under a changing climate, particularly species native to boreal and Mediterranean biomes. Overall, hotspots of naturalization risk defined by climatic suitability alone, or by a combination of climatic suitability and appropriate land cover, are projected to increase by up to 102% or 64%, respectively. Main conclusions Our results suggest that the risk of naturalization of European garden plants will increase with warming climate, and thus it is very likely that the risk of negative impacts from invasion by these plants will also grow. It is therefore crucial to increase awareness of the possibility of biological invasions among horticulturalists, particularly in the face of a warming climate.